2022
DOI: 10.3389/fmars.2022.899812
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Trophic Tracer Analyses of Subarctic Rhodolith (Lithothamnion glaciale) Bed Trophodynamics Uncover Bottom-Up Forcing and Benthic-Pelagic Coupling

Abstract: We paired a survey of cryptofaunal abundance and rhodolith morphology with lipid, fatty acid, and stable isotope analyses to quantify nutritional patterns and trophic linkages of six dominant echinoderm, bivalve, gastropod, and polychaete species, two macroalgal species, seawater, and underlying sediment in a large (>500 m2) rhodolith (Lithothamnion glaciale) bed in southeastern Newfoundland (Canada). We found high densities of chitons (Tonicella marmorea and T. rubra) and daisy brittle star (Ophiopholi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 135 publications
(200 reference statements)
5
1
0
Order By: Relevance
“…We also showed that rhodolith shape distribution was similar among pebble-nucleated and non-nucleated rhodoliths, with ~70% of compact shapes, while shell-nucleated rhodoliths were mostly bladed (59%) or elongate (20%) but seldom compact. Our finding that the majority of rhodoliths at both study sites were nonetheless non-nucleated and compact in shape parallels observations in other sections of the St. Philip's bed since 2012 [30,36,50]. Predominantly compact shapes have also been documented in arctic [72,73], temperate [71,74], and tropical [75,76] rhodolith beds.…”
Section: Rhodolith Bed Structuresupporting
confidence: 87%
See 3 more Smart Citations
“…We also showed that rhodolith shape distribution was similar among pebble-nucleated and non-nucleated rhodoliths, with ~70% of compact shapes, while shell-nucleated rhodoliths were mostly bladed (59%) or elongate (20%) but seldom compact. Our finding that the majority of rhodoliths at both study sites were nonetheless non-nucleated and compact in shape parallels observations in other sections of the St. Philip's bed since 2012 [30,36,50]. Predominantly compact shapes have also been documented in arctic [72,73], temperate [71,74], and tropical [75,76] rhodolith beds.…”
Section: Rhodolith Bed Structuresupporting
confidence: 87%
“…We showed that the rhodolith bed at both sites was structurally stable throughout the survey, containing >90% of live and dead rhodoliths and coarse biogenic sediments, as well as similar rhodolith densities (~822 individuals m −2 ) and biomasses (~11.5 kg rhodoliths m −2 ) in any given season. Such rhodolith densities and biomasses within the 15-20 m depth range (1) parallel the ~858 rhodoliths m −2 reported by Gagnon et al [30] for a shallower (8 to 10 m deep) portion of the same bed sampled four years before the present study, and (2) are up to twice lower than the peak 19.5 kg rhodoliths m −2 measured in other portions of the bed within the 8-15 m depth range four years before [30] and four years after [50] the present study. That rhodolith biomass varies spatially within the bed despite a homogenous rhodolith density, indicates that rhodolith size varies across the bed.…”
Section: Rhodolith Bed Structuresupporting
confidence: 85%
See 2 more Smart Citations
“…However, the fatty acid composition of polar lipids observed throughout the year likely reflects the acclimation of organisms to the low temperatures observed in the fjord (temperature < to 0.5°C throughout the year at 17 m, Sejr et al, 2022). The strong relative contributions of PUFAs observed in H. arctica, M. discors, and Mya truncata (i.e., >47%) are similar to those observed in other studies that also found an effect of cold temperature on the lipid composition of cell membranes of Arctic/sub-Arctic bivalve species (Gaillard et al, 2015;Hacker Teper et al, 2022;Thyrring et al, 2017).…”
Section: Physiological Indicatorssupporting
confidence: 80%